The Socio economic significance of women participation in tourism development and promotion: a case study of New Bussa Community Area of Niger State - Chikezie., J.; Kolawole G.T.; Omotayo O.L.; Adedeji E.O.; Deji Joshua; Onihunwa, John Ojo; Elizabeth Abidemi Akintade (Technium Social Sciences Journal, 2020)
This study focuses on socio economic significance of women participation in tourism development and promotion in Bussa. Sampling techniques that were used in this research work include cluster and random sampling methods. New Bussa community was divided into four areas. Hundred questionnaires were administered to the study areas to get the data needed; The data collected was subjected to statistically computation using descriptive analysis such as table, and simple percentage. The results highlighted some types of leisure they engage in and whether their works disturb them. 65% of the respondents agreed that they participate in leisure activities followed by those that chose at times represent 30%. On the activities they engaged in 50% of the respondents have indoor as their leisure engagement while 31.6% of the respondents engage in Outdoor activities. On whether their jobs affect leisure activities 61.6% of the respondents were of the opinion that work does not disturb them. While on whether women help in community when they arrived, 63.3% of the respondents supported yes option while 31.6% of the respondents supported fairly. On the issue of women employment in the community 81.6% of the Respondents agreed that women are being given employment while the results also indicate the social significance of women participation in leisured based on the case of social enlightenment of women, 90% of the respondents agreed that it socializes them while 1.6% said they were not sure. On the issue of well-being 90% of the respondents agreed that participation of women bring their well-being while 3.3% claimed they were not agree and 1.6% said it is fairly. Challenges It shows that women are having challenges in leisure and tourism participation the respondents agreed that they could not be involved in tourism because of financial challenges, 85% and religious activities, 68.3% while 13.3% of the respondents claimed that it used to be sometimes while 1.6% of the respondents claimed that the traveling is not encouraging That the women participation should be adequately funded both with the public and private sectors to boost the economic and social life of Bussa people. However the results recommend that if tourism is to be promoted and to be internationally recognized the issue of women must not be left out in all ramifications.